A comparative analysis of predictors of teacher self‐efficacy in student engagement, instruction and classroom management in Nordic, Anglo‐Saxon and East and South‐East Asian countries. Issue 1 (8th December 2020) - Fackler, Sina; Sammons, Pamela; Malmberg, Lars‐Erik
Abstract : Going beyond previous studies, we investigated differential effects of teacher self‐efficacy (TSE) across the three basic dimensions of educational equality in student engagement, instructional strategies and classroom management in East and South‐East Asian, Anglo‐Saxon and Nordic country clusters in a cross‐cultural analysis. It was found that all three domains of TSE show different patterns of associations in relation to teacher, classroom, principal and school predictors across the three country clusters. Most variation occurred within the classroom and principal predictors, whereas the teacher and school predictors were more homogeneously related to the three country clusters and the three domains of TSE. However, there were more similarities between the Nordic and Anglo‐Saxon clusters than the East and South‐East Asian clusters and any of the other two. Cultural values, as found in the GLOBE study and by Hofstede, were used as a cultural framework to interpret the differences occurring in the country clusters.